China's Public Diplomacy. - D'Hooghe, Ingrid (Diplomatic studies., 2014)
In China's Public Diplomacy, Ingrid d'Hooghe provides a thorough analysis of how China's approach to public diplomacy is shaped by the country's political system and Chinese culture.